Tuberculosis in Staff and Students of Patan Hospital - Shrestha, Poojan; Shakya, Mila; Caws, Maxine; Shrestha, Surendra; Karki, Bibek; Shrestha, Shreejana; Karki, Dan Bahadur; Maharjan, Bhagwan; Shrestha, Bhawana; Arjyal, Amit; Karkey, Abhilasha; Prajapati, Krishna G.; et al. (Journal of Nepal Health Research Council, 2018)
Background: There is a high risk of occupational exposure to tuberculosis among healthcare workers in endemic countries. Regular screening for tuberculosis among healthcare workers is not carried out in Nepal. Infection control measures are also not routinely implemented. The aim of this study was to determine the prevalence of active tuberculosis among staff/students at Patan Hospital. Methods: Participants were given a self-administered questionnaire and invited to undergo chest radiography. Cases were scored and reviewed based on predetermined criteria, and presumptive tuberculosis cases were invited to undergo sputum smear and culture. Participants were categorized according to the extent of patient contact and asked about history of tuberculosis medication. Results: Among 560 participants, 76.8% had direct contact with patients. Fifty-eight (10.4%) gave history of cough >2 weeks. Based on symptom history and chest radiography, 20.0% (n=112) cases were reviewed, and 12.5% (n=14) of those reviewed had sputum tested for acid-fast bacilli. One participant had culture-positive tuberculosis. Fifty participants (8.9%) reported tuberculosis in the past, among which 42.0% (n=21) occurred after employment at Patan Hospital and 42.0% before joining Patan Hospital. Security staff, radiology technicians and ward cleaning staff had the highest proportion of cases with a history of tuberculosis.History of tuberculosis medication had no relation with age, sex, education, body mass index and smoking.The incidence rate of tuberculosis at Patan Hospital was 3.6 per 1000 person-years. Conclusions: Overall incidence of tuberculosis among healthcare workers is noteworthy. However, this study suggests when symptomatic tuberculosis occurs in healthcare worker at Patan Hospital, it is diagnosed and there is not a large pool of undiagnosed tuberculosis.